Peran Masjid dalam Penyebaran Toleransi : The Role of Mosques in Spreading Tolerance - Rohman, Baeti; Maulana, Fikri; Abidin Riam , Zaenal; juraidi, ahmad (Jurnal Bimas Islam, 2023)
Islam is a religion that does not close itself to diversity, Islamic teachings make tolerance an attitude in dealing with differences, this attitude is reflected in Islamic principles which believe that religion is not something that can be forced and then confirmed through the sacred doctrine that there is no compulsion in religion. The mosque has its own privileges in the Islamic world, the function of the mosque cannot be reduced only as a place of worship, more than that the mosque plays an important role in the spread of Islam through da'wah. Islam encourages da'wah to be carried out gently by withholding messages of peace and tolerance. This study aims to understand the contribution of mosques in spreading tolerance by using a literature review methodology. The results of the study show that mosques have an important role in spreading tolerance, the spread of tolerance through mosques is realized because mosques function as da'wah centers in the Islamic world. The preaching of tolerance is packaged in two forms, namely preaching tolerance verbally and preaching tolerance in action. In the long run, the message of tolerance that is often conveyed through mosques is expected to be able to maintain the harmony of life among religious communities and the nation which consists of various religious and ethnic backgrounds.